2023
DOI: 10.3389/felec.2023.1034082
|View full text |Cite
|
Sign up to set email alerts
|

Research on optimal coil configuration scheme of insulator relay WPT system

Abstract: This paper presents the optimized structure of the multi-relay coils insulator of WPT system. With the rapid development of the smart grid, on-line monitoring devices in the transmission tower have been widely used. However, the power supply problem has become an important bottleneck in the development of transmission tower intelligent sensing technology. Hence, the multi-relay coils wireless power transfer technology has been proposed to supply for the tower monitoring equipment in this paper. Compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Preliminary studies have found that artificial detuning between the Rx and Tx circuits can affect the system's resonant frequency (Li and Huang, 2022;Liu et al, 2022;Wang et al, 2023). When the detuning rate is sufficiently high, the resonant frequency-hopping phenomenon occurs.…”
Section: Effects Of Detuning On the Frequencymentioning
confidence: 99%
“…Preliminary studies have found that artificial detuning between the Rx and Tx circuits can affect the system's resonant frequency (Li and Huang, 2022;Liu et al, 2022;Wang et al, 2023). When the detuning rate is sufficiently high, the resonant frequency-hopping phenomenon occurs.…”
Section: Effects Of Detuning On the Frequencymentioning
confidence: 99%